Origins of the Differences in Political Systems of the Central Asian States: Threat Perception in the Perestroika Period - Tomohiko Uyama (Международная аналитика)
Using the “path-dependence” concept and D. Slater’s thesis on the consolidation of elites around national threats, the author examines the factors inﬂ uencing the formation of diﬀ erent authoritarian political systems in the Central Asian states. A critical aspect of the formation of political systems in this region was the events from the mid-1980s to the collapse of the Soviet Union. In terms of the structure of the study, the article consistently examines how interethnic and other political conﬂ icts demonstrated the (un)ability of leaders to cope with crises. In particular, it shows that the inability to cope with political challenges in Kyrgyzstan marked the beginning of “pluralism by default.” Moscow’s involvement in the personnel issues in the republics, especially in Uzbekistan and Kazakhstan, undermined local elites and increased the overall sense of threat to political stability, which eventually rallied elites and gave rise to expectations of a strong leader. We also note that a notably fortiﬁ ed power hierarchy was established where the new national leader perceived threats from his political rivals (in Uzbekistan). Conversely, the existence of a strong opposition prevented the rapid establishment of authoritarianism. In Tajikistan, for example, a split of the elite led to a civil war, but due to the greater stability of its governmental wing, the president subsequently managed to establish a hard authoritarian regime. In Turkmenistan, the country’s leader took advantage of the lack of threats to establish a dictatorship. Thus, external challenges contribute to the consolidation of elites, while the risks of internal competition contribute to the concentration of power in the hands of an authoritarian leader. On the contrary, prolonged threats divide elites, lead to mass conﬂ icts or the formation of a relatively democratic but unstable system of state power.